2022
DOI: 10.1007/s40489-022-00329-3
|View full text |Cite
|
Sign up to set email alerts
|

Little Evidence for Conservative Toe Walking Interventions in Autism Spectrum Disorders: a Systematic Review

Abstract: This systematic review summarizes the evidence about toe walking (TW) interventions in persons with autism. Following the PRISMA guidelines, a systematic search of MEDLINE, CINAHL, PsycINFO, The Cochrane Library, Google Scholar, and Opengrey was performed. Nine articles (all case reports or case series) were included. Methodological quality was assessed using the Mayo Evidence-Based Practice Centre tool. The included studies considered 17 subjects (16 males; age range: 4–15 years). All studies reported a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…With regard to therapeutic possibilities and indications, a recent systematic review summarized the evidence on conservative, pharmacological, and surgical interventions for TW in individuals with ASD [ 61 ]. The authors included nine papers, all with a case study—case report study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to therapeutic possibilities and indications, a recent systematic review summarized the evidence on conservative, pharmacological, and surgical interventions for TW in individuals with ASD [ 61 ]. The authors included nine papers, all with a case study—case report study design.…”
Section: Discussionmentioning
confidence: 99%
“…Serial casting +/− orthoses and behavioral interventions (i.e., using acoustic feedback associated with positive reinforcement, or a wristband as a discriminative stimulus) were the most studied interventions. Moreover, despite pharmacological and surgical interventions being used to treat TTB in persons with autism in clinical practice [ 62 ], no studies that assess effectiveness of pharmacological and surgical interventions were found [ 61 ].…”
Section: Discussionmentioning
confidence: 99%